2017
DOI: 10.4142/jvs.2017.18.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Use of stem-cell sheets expressing bone morphogenetic protein-7 in the management of a nonunion radial fracture in a Toy Poodle

Abstract: A 12-year-old castrated Toy Poodle was referred to the Kangwon National University Animal Hospital with an oligotrophic nonunion fracture in the distal 1/3 of the left radius and an intact ulna. After fixation by a locking plate and screws, adipose-derived mesenchymal stem-cell sheets expressing bone morphogenetic protein 7 (BMP-7) were transplanted to the fracture site to enhance the healing activity. The fracture was healed at 9 weeks after surgery. In the present case, the mesenchymal stem-cell sheets expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Growth factors as FGF-2, TGF-β combined with ADSC on a polysaccharide-based tissue engineered periosteum have shown promising results as they promote a more stable harvesting and integration in murine models [ 41 ]. Furthermore, different studies proved the increased osteogenic properties of transgenic ADSCs overexpressing bone morphogenetic protein 2 (BMP2) [ 42 ] or BMP-7 [ 43 ] in promoting bone healing of long-bones defects. Nonetheless, despite the high transfection efficiency and yield in the transgene expression that they enable, the use of adenoviral vectors for gene transfer seems to complicate a rapid translation of such protocols in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors as FGF-2, TGF-β combined with ADSC on a polysaccharide-based tissue engineered periosteum have shown promising results as they promote a more stable harvesting and integration in murine models [ 41 ]. Furthermore, different studies proved the increased osteogenic properties of transgenic ADSCs overexpressing bone morphogenetic protein 2 (BMP2) [ 42 ] or BMP-7 [ 43 ] in promoting bone healing of long-bones defects. Nonetheless, despite the high transfection efficiency and yield in the transgene expression that they enable, the use of adenoviral vectors for gene transfer seems to complicate a rapid translation of such protocols in the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-7 expressing stem-cell sheets were applied in the previous studies (2022). In a previous report, BMP-7 overexpressing adenovirus vector was used to transfect mesenchymal stem cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, BMP-7 overexpressing adenovirus vector was used to transfect mesenchymal stem cells (22). In a non-union fracture model, BMP-7 expressing mesenchymal stem cells enhanced bone regeneration (20). Similarly, BMP-7 expressing stem cells produced enhanced bone healing in critical-sized defects when compared with the control stem cell sheets (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concerns that BMP treatment does not return bone to normal form and function after remodelling have been reported. 9 In veterinary medicine, the use of BMP has been successful in the treatment of nonunion long bone fractures, [10][11][12][13][14][15] mandibular reconstruction [16][17][18][19] and arthrodesis. [20][21][22] Massie and colleagues reported the use of compression-resistant matrix (CRM) infused with recombinant human bone morphogenetic protein-2 (rhBMP-2) in dogs and the short-term study demonstrated that rhBMP-2 is safe and effective, with 9 of 11 treated fractures returning to full function and the remaining 2 fractures having acceptable function.…”
Section: Introductionmentioning
confidence: 99%